Reconstitution of the immune system and clinical correlates after stem cell transplantation for systemic sclerosis - Kawashima-Vasconcelos, Marianna Y.; Santana-Gonçalves, Maynara; Zanin-Silva, Djúlio C.; Malmegrim, Kelen C. R.; Oliveira, Maria Carolina (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is a chronic autoimmune disease that includes fibrosis, diffuse vasculopathy, inflammation, and autoimmunity. Autologous hematopoietic stem cell transplantation (auto-HSCT) is considered for patients with severe and progressive SSc. In recent decades, knowledge about patient management and clinical outcomes after auto-HSCT has significantly improved. Mechanistic studies have contributed to increasing the comprehension of how profound and long-lasting are the modifications to the immune system induced by transplantation. This review revisits the immune monitoring studies after auto-HSCT for SSc patients and how they relate to clinical outcomes. This understanding is essential to further improve clinical applications of auto-HSCT and enhance patient outcomes.